Exploring the Concept of Muslim Friendly Tourism - Muslim, Aini Khalida (The international journal of religious tourism and pilgrimage, 2022)
Most researchers face problems investigating Muslim-friendly destinations when they become confused with overlapping terms that seem to convey the same concepts, such as Islamic Tourism, Halal Tourism, and Muslim Friendly Tourism. This study discusses the concepts, purpose, target customers, destinations, products, and services to fill the gap in understanding the differences between the three terms from the perspective of Muslim and non-Muslim tourists. This study also applies a systematic literature review (SLR) method to filter and locate papers related to Muslim Friendly Tourism from 2015 to 2020. The analysis is based on the year the article was published, the publisher’s name, research type and the country of study. Only three papers actually discuss Muslim Friendly Tourism concepts. This means that research of Muslim Friendly Tourism concepts is poorly explored and needs further investigation. Surprisingly, no researcher has discussed the differences between Islamic tourism, Halal tourism, and Muslim Friendly Tourism while the findings indicate the differences between these three terms.